Selection policy and immigrants' remittance behaviour - Stephane Mahuteau; Matloob Piracha; Massimiliano Tani (University of Kent, School of Economics, 2010)
This paper analyses the impact of a change in Australia's immigration policy, introduced in the mid-1990s, on migrants' remittance behaviour. More precisely, we compare the remittance behaviour of two cohorts who entered Australia before and after the policy change, which consists of stricter entry requirements. The results indicate that those who entered under more stringent conditions the second cohort have a lower probability to remit but, if remitting, they tend to remit, on average, a higher amount than those in the first cohort. We also find significant time and region effects. Contrary to some existing evidence, time spent in Australia positively affects the probability to remit while in terms of regional effects, South Asians remit the highest amount. We discuss intuitions for the results in the paper.
Keywords: F22; F24; J61; 330; remittances; immigration; selection policy; Migrationspolitik; Einwanderungsrecht; Reform; Rücküberweisung (Migranten); Einwanderung; Australien